Brachial Plexus Anaesthesia: A Comparative Study on Supraclavicular Subclavian Perivascular Technique with the Axillary Transarterial Technique with A Tourniquet (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Objectives : To make a comparative evaluation of efficacy of brachial plexus blockade between supraclavicular subclavian perivascular technique and axillary transarterial technique with a tourniquet and also to compare the latency & potency of the block, to ascertain the risks of complications between the techniques and to compare the haemodynamic stability of the patient.Methods : For this purpose a total of 100 undergoing surgery for distal to the midarm. They were randomly selected by odd and even numbering method. These patients were divided into two groups (Group A: subclavian perivascular supraclavicular technique bearing all the odds numbers and Group B: transarterial axillary technique with a tourniquet bearing all the even numbers; fifty patients in each group.Results : The only exception is the mean on set time of sensory block was 11.0±2.6 minutes and 14.3±2.1 minutes in Group A and Group B respectively. The mean on set time of motor block were 18.3±3.9 minutes in Group A and 21.4±3.2 minutes in Group B. So the mean on set time of sensory block and motor block were statistically significant (p0.05) difference was found in the present study. Adequate efficacy of block were predominate in both groups and no significant (p>0.05) difference was found. The level of satisfaction of surgeon and it was found that 92.0% in Group A and 94.0% in Group B were satisfied. Patients co-operation was found 92.0% and 94.0% in Group A and Group B respectively. No significant (p>0.05) difference were found in terms of surgeon satisfaction and patients cooperation between two groups.Conclusion : It can be concluded that the supraclavicular subclavian perivascular technique and axillary transarterial technique with a tourniquet both are equally effective and safe method for providing brachial plexus block distal to midarm (Lower half of the arm, elbow, forearm and hand).Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 21-26